Gestão de Unidades de Conservação e Terras Indígenas entre disputas, tensões e conflitos: as situações da REBIO Gurupi e das TIs Alto Turiaçu,Awá e Caru no Maranhão - Souza, Laís Gonçalves de (2017)
This dissertation has the objective of reflecting on disputes, tensions and conflicts involving different points of view regarding management of the Gurupi Biological Reserve and Alto Turiaçu, Awá and Caru indigenous lands, where Awá-Guajá, Ka’por and Tenetehara indigenous peoples live. This research’s focuses of analysis are: a) dispute processes associated with lands traditionally occupied by the aforementioned indigenous peoples in the western Maranhão; b) existing tensions and conflicts in the Zé dos Santos Advisory Council of the Gurupi Biological Reserve; and c) positioning of Alto Turiaçu and Caru indigenous lands in the face of official politics related to management of its territories. For this purpose, I analyzed official documents concerning the reserve and surrounding indigenous lands, interviewed social agents involved in discussion about these areas and I went to Zé dos Santos Advisory Council meeting at the Gurupi Biological Reserve and of the Ka’por people together with state education organs. Analysis of this material enabled construction of critical reflection regarding forms of territorial division and management established by acts of the “State”, as well as forms of officially instituted with the objective of legitimizing such acts. Moreover, it was also possible to reflect about forms of “participation” and management suggested by indigenous people which would tear through the bureaucratic dimension established by the State.